Exploring the mechanical performance and durability of recycled concrete for modern civil structures: a literature review - Suharwanto Suharwanto (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study investigates the mechanical performance and durability of recycled aggregate concrete (RAC) as an alternative material for modern civil structures. Using a systematic literature review of recent empirical and conceptual studies, the research evaluates how recycled concrete aggregates (RCA) influence compressive, tensile, and flexural strengths, elastic modulus, porosity, and long-term durability under diverse environmental conditions. The findings confirm that although RAC typically demonstrates lower compressive strength, tensile resistance, and stiffness compared to natural aggregate concrete (NAC), these limitations are not intrinsic. They can be effectively mitigated through controlled RCA processing, pre-saturation treatments, supplementary cementitious materials, and fiber reinforcement. Regarding durability, RAC generally exhibits higher water absorption, permeability, and susceptibility to chloride ingress, carbonation, and freeze–thaw damage. Nevertheless, optimized mix designs and appropriate curing regimes can significantly improve its performance, making it suitable for structural applications at low to moderate RCA replacement ratios. Long-term challenges such as creep, shrinkage, fatigue, and fire resistance remain more pronounced in RAC but can be addressed with advanced mix engineering and conservative design practices. This review concludes that RAC is not merely a substitute for NAC but a sustainable material with distinct performance characteristics that require tailored strategies. By integrating technical innovations with quality control and policy support, RAC can contribute to sustainable infrastructure development while maintaining safety and reliability.